"If You Show Who You are, Then They are Going to Try to Fix You": The Capitals and Costs of Schooling for High-Achieving Latina Students. Issue 1 (2nd January 2017) - Locke, Leslie Ann; Tabron, Lolita A.; Venzant Chambers, Terah T.
Abstract : Schools are supposed to be places where students learn academic and technical skills while also expanding their social networks. Although much research exists that examines academic achievement from a variety of lenses, schools and educators continue to lack insight into the various strengths—or capital—students bring with them to school alongside the barriers—or costs—they face once there. To help bridge the gap between the extant research and what is practiced in schools, we provide insight into what educators can do to capitalize on students' strengths and minimize the barriers to achievement. This article draws from two theoretical frameworks, Community Cultural Wealth (CCW) and Racial Opportunity Cost (ROC), and two qualitative research projects that examined Latina high school students' academic achievement from a capitals and costs perspective. Although significant research has identified assets-based approaches to schooling, our results indicate that the interplay between the norms of the school and the norms the students embraced played a critical role in terms of creating conditions for a positive school experience. Based on our findings, we offer recommendations for educators to address the costs that students experience.